2015
DOI: 10.1111/ijs.12609
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of 24-H ABPM in Acute Ischemic Stroke for Short-, Medium-, and Long-Term Outcome: A Systematic Review and Meta-Analysis

Abstract: Higher systolic and diastolic blood pressure levels derived with ambulatory blood pressure monitoring were associated with poor outcome. The same was not found for higher casual blood pressure measurements on admission, and it is possible that ambulatory blood pressure monitoring conveys better prognostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…() too, noted an association between lower BP and death . Recently, a meta‐analysis of several relatively small studies (Kakaletsis et al., ) investigated the association between outcome in acute IS and BP measured by ambulatory monitoring methods during the first 24 hr of admission and found that elevated pressures predicted poor outcome, in the form of either death or poor functional outcome.…”
Section: Introductionmentioning
confidence: 99%
“…() too, noted an association between lower BP and death . Recently, a meta‐analysis of several relatively small studies (Kakaletsis et al., ) investigated the association between outcome in acute IS and BP measured by ambulatory monitoring methods during the first 24 hr of admission and found that elevated pressures predicted poor outcome, in the form of either death or poor functional outcome.…”
Section: Introductionmentioning
confidence: 99%
“…High BP variability in the acute phase of ischemic stroke has also been reported to lead to poor outcomes because such variability during the first 72 hours of stroke onset promotes hemorrhagic transformation and increases the risk of lesion growth and recurrence 9,10 . However, a systematic review and meta-analysis found no association between BP variability during the first 24 hours of admission and stroke outcome 11 . Previous studies have explained some of these conflicting results.…”
mentioning
confidence: 98%
“…A meta-analysis of studies of acute ischemic stroke patients admitted within 24 hours of onset and undergoing ABPM within 24 hours of admission showed that both high systolic and diastolic BP levels derived from ambulatory BP monitoring were associated with poor short-, intermediate-, and long-term outcomes, but the same was not found for casual (clinic) BP measurements. 45 Additionally, in a study of 128 initial acute stroke patients who underwent ABPM within 24 hours of stroke onset and computerized tomography scans of the brain on both admission to the hospital and 5 days later, multivariate logistic regression analysis showed that each 0.1 mm Hg/minutes increase in the time rate of 24 hours SBP variation was associated with a 13.9% increased probability of presence of brain edema.…”
Section: Ambulatory Bp Monitoring In Evaluating Outcomes For Recurrenmentioning
confidence: 99%